Software engineering and knowledge engineering: Theory and practice : Selected papers from 2012 International Conference on Software Engineering, Knowledge Engineering and Information Engineering (SEKEIE 2012) - Zhang, Wei (Advances in Intelligent and Soft Computing, 2012)
2012 International Conference on Software Engineering, Knowledge Engineering and Information Engineering (SEKEIE 2012) will be held in Macau, April 1-2, 2012 . This conference will bring researchers and experts from the three areas of Software Engineering, Knowledge Engineering and Information Engineering together to share their latest research results and ideas.   This volume book covered significant recent developments in the Software Engineering, Knowledge Engineering and Information Engineering field, both theoretical and applied. We are glad this conference attracts your attentions, and thank your support to our conference. We will absorb remarkable suggestion, and make our conference more successful and perfect.